2018
DOI: 10.1186/s13075-018-1620-1
|View full text |Cite
|
Sign up to set email alerts
|

Cortical bone loss is an early feature of nonradiographic axial spondyloarthritis

Abstract: BackgroundIn the present study, we investigated bone geometry, microstructure, and volumetric bone mineral density (vBMD) in a cohort of patients with nonradiographic axial spondyloarthritis (nr-axSpA) in order to define the early bone changes occurring in axial spondyloarthritis (axSpA) and to define potential factors for deterioration of bone microstructure.MethodsPatients with axSpA (n = 107) and healthy control subjects (n = 50) of similar age and sex were assessed for geometric, volumetric, and microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Unsurprisingly, the parameters of systemic inflammation (i.e., increase in the C-reactive protein) have also been associated with low BMD [107]. The role of systemic inflammation as a determinant for generalized bone loss is also supported by the demonstration of low cortical BMD, and the area and thickness measured by HRpQCT [118]; once again, this process was reported as an early event.…”
Section: Spondyloarthritis and Psoriatic Arthritismentioning
confidence: 99%
“…Unsurprisingly, the parameters of systemic inflammation (i.e., increase in the C-reactive protein) have also been associated with low BMD [107]. The role of systemic inflammation as a determinant for generalized bone loss is also supported by the demonstration of low cortical BMD, and the area and thickness measured by HRpQCT [118]; once again, this process was reported as an early event.…”
Section: Spondyloarthritis and Psoriatic Arthritismentioning
confidence: 99%
“…In another study by Neumann et al, HR-pQCT showed pronounced bone loss in the cortical area, cortical thickness, and cortical BMD in patients with nr-axSpA as compared to controls. However, trabecular vBMD did not differ between patients and controls (81). Patients with short disease duration (<2 years) also showed a significant reduction in cortical thickness and cortical area when compared with controls, and the decrease in cortical thickness was more prominent in long-term patients (disease duration >2 years).…”
Section: High-resolution Peripheral Quantitative Computed Tomographymentioning
confidence: 70%
“…HR-pQCT measures the trabecular and cortical compartments separately at the tibia and radius, allowing measurement of large portions of distal bones with good spatial resolution and minimal irradiation (16,17). HR-pQCT measures microarchitecture parameters such as trabecular thickness, number and distribution, and cortical porosity of the tibia and radius, thus resembling a virtual bone biopsy of the peripheral bone (16,79,81,82). It was previously argued that osteoporosis in patients with axSpA primarily affects the axial skeleton (23,83).…”
Section: High-resolution Peripheral Quantitative Computed Tomographymentioning
confidence: 99%
“…46 According to the results of Neumann et al, the use of this tool could become crucial for diagnosing early changes in patients with nonradiographic AS because it can detect cortical deterioration that occurs within the first 2 years of the disease. 47 Like DEXA, HR-pQCT can also be used to investigate lean mass by dedicated software separating fat, muscles, and bones and selecting appropriate density thresholds on a single slice of interest. Parameters like muscle cross-sectional area, muscle density, and intramuscular adipose tissue area can then be collected.…”
Section: Dual-energy X-ray Absorptiometrymentioning
confidence: 99%